The Church and Poverty in Africa - Kehinde Olusanya (African Theological Journal for Church and Society)
This paper focuses on the perennial challenge of poverty in Africa and the role of the church in providing lasting solutions for this challenge. In the pursuance of the thesis of this study, which is that the church has an ethical role to play in ameliorating, if not eradicating the problem of poverty in Africa, the writer considers conceptualizing poverty in Africa, Biblical understanding of poverty, ethical analysis of the responsibility of the church in combating poverty in Africa, and homiletical implications of the church’s role in the challenge of poverty in Africa as objectives. The writer approaches the concept of poverty from the perspective of the Bible and argues that the perspective of scripture is that poverty exists and the rich should care for the poor. The writer also argues that while both the Old and The New Testaments encourage a benevolent attitude from the rich towards the poor, the poor should not be lazy in terms of work and personal efforts. The paper examines the ethical responsibilities of the church, concluding that the responsibilities of the church are sectioned into theological, educational, and pastoral responsibilities. The writer argues that these responsibilities have homiletical implications. The implications are that the church should have more prophetic preaching. This prophetic preaching should be biblical, and church’s preachers should have lives that agree with their messages. There is a connection between the pulpit and the growing rate of poverty in Africa; the writer, therefore, recommends that the church does more in the war against poverty on the African continent.